Ethical dilemmas at the end of life: a reflection from the Philosophical Perspective of Luigina Mortari - Vitória Pessoa Nogueira; Marília Alves Furtado; Vera Lúcia Mendes de Paula Pessoa; Viviane Magalhães Pereira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to reflect on the ethical dilemmas involved in the care of patients at the end of their lives. Methods: this is a theoretical-reflective study based on the ethics of care proposed by Luigina Mortari. Results: discussing care involves addressing the ways of being inherent to human existence and understanding the unique characteristics of this condition. Ethical care constitutes an action driven by interest in the other and by the perception of their need. Ethical dilemmas are a part of end-of-life care, making it essential to maintain respectful assistance that considers the patient's autonomy, using strategies for expressing their wishes, and ensuring continuous clear and empathetic communication among all those involved in providing care. Final Considerations: issues related to being, stemming from one's reality of dependency and vulnerability, contribute to the emergence of ethical dilemmas present in care actions.